2011
DOI: 10.3855/jidc.2098
|View full text |Cite
|
Sign up to set email alerts
|

Utility of an interferon-gamma release assay as a potential diagnostic aid for active pulmonary tuberculosis

Abstract: Introduction: Sensitivity, specificity, early confirmation and obtaining an optimal specimen are challenging problems in active tuberculosis (TB) diagnosis. Interferon-gamma release assay (IGRA) is a good indicator for latent TB but can it be useful as a diagnostic tool for active TB? This study was designed to address these challenges and assess the potential of IGRA as a diagnostic indicator of active pulmonary TB by comparing it with other MT diagnostic conventional methods and molecular methods. Methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
5
0
2
Order By: Relevance
“…The performance of IGRAs has been examined in numerous studies of immunocompetent subjects, HIV-infected individuals, and children. Overall, the data in the literature indicates that both IGRAs have a better specificity and correlation with exposure to MTB than the TST and equal or greater sensitivity [4]. The greater specificity of IGRAs in comparison to the TST is very important for the correct identification of infected subjects and for the administration of preventive therapy.…”
Section: Interferon-gamma Release Assays (Igras)mentioning
confidence: 86%
“…The performance of IGRAs has been examined in numerous studies of immunocompetent subjects, HIV-infected individuals, and children. Overall, the data in the literature indicates that both IGRAs have a better specificity and correlation with exposure to MTB than the TST and equal or greater sensitivity [4]. The greater specificity of IGRAs in comparison to the TST is very important for the correct identification of infected subjects and for the administration of preventive therapy.…”
Section: Interferon-gamma Release Assays (Igras)mentioning
confidence: 86%
“…Unlike these reports, a recently published systematic review using latent class modelling to assess the utility of TST and QFT-GIT for LTBI diagnosis in different population groups showed a low sensitivity (52%) but high specificity (97%) of QFT-GIT to diagnose LTBI [ 28 ]. Even active TB studies have reported low sensitivity but varying specificity for QFT-GIT [ 29 , 30 ]. Furthermore, as the strength of TST product is increased, the induration cut-off for a positive TST gets reduced and is closer to positivity of QFT-GIT.…”
Section: Discussionmentioning
confidence: 99%
“…1,15 On the other hand, the specificity of IGRA has been between 67.4% to 98.1% in the immunocompetent population. 16,17 Only 5% of evaluated patients had a positive TST, despite prior BCG vaccination in all of our subjects during childhood, which might potentially lead to false-positive TST results. Our data are low compared with previous reports that show a 24% positive outcome.…”
Section: Discussionmentioning
confidence: 90%